Time‐Lapse Acquisition of Both Freely Secreted Proteome and Exosome Encapsulated Proteome in Live Organoids’ Microenvironment - Haoni Yan; Aynur Abdulla; Aiting Wang; Shuyu Ding; Manlin Zhang; Yizhi Zhang; Tsz Yui Zhuang; Leqi Wu; Yan Wang; Rongrong Ren; Lai Jiang; Xianting Ding (Advanced Science)
Abstract Proteomic communications in neighboring microenvironments during early organ development is a dynamic process that continuously reshapes human embryonic stem cells (hESCs) developmental fate. Such dynamic proteomic alteration in the microenvironment consists of both freely secreted proteome and exosome‐encapsulated proteome. Simultaneous monitoring of the time‐lapse shift of both proteomes with live organoids remains technically challenging. Here, a continuous organoid secretion/encapsulation proteome tandem LC‐MS/MS (COSEP‐LCM) is introduced, which permits time‐lapse monitoring of proteomic alterations both in free secretion form and in exosome encapsulated form at live organoids’ microenvironment. Continuous growth of human cerebral organoids (COs) and free‐secretion/exosome‐encapsulation proteomics acquisition with COSEP‐LCM for 60 days is demonstrated. SERPINF1, F5, and EFNB1 are initially enriched inside exosomes as encapsulated excretion and then gradually enriched outside exosomes as freely secreted excretion, while C3 is initially enriched outside exosomes as freely secreted excretion and gradually enriched inside exosomes as encapsulated excretion. Such dynamic excretion pattern paradigm shift may imply critical developmental strategy evolution during early human cerebral development. COSEP‐LCM offers a platform technique for continuous inside/outside exosome proteomics co‐analysis in live organoids’ microenvironment.